Analysis of the Role of Bappeda in Regional Development Planning (Case Study of Maternal Mortality in Batu Bara Regency in 2016) - Firman Pane; Siti Mardiana; Rudi Salam Sinaga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The aims of this study is to find the Role of Bappeda in Regional Development Planning. This study use descriptive qualitative approach. The role of the Bappeda of Batu Bara Regency in reducing maternal mortality from the government, health workers, and the community is quite good. The number of health workers in this case, namely midwives, has been widely spread in the Batu Bara Regency area. The village midwife service in Batu Bara Regency was also developed starting from the lifestyle of the village community which cannot be separated from environmental, cultural, economic and socio-cultural factors.Informational Roles (Informational Role) on the role Bappeda has mobilized all health workers who have special competencies, especially skills in handling emergency cases in dealing with the main causes of maternal death. The role of cadres in reducing maternal mortality in the community is very much needed. In terms of quality and quantity, the cadres involved should be able to meet the needs. The decision-making role (Decisional Role) is carried out by the Batu Bara Regency Bappeda with other sectors, namely the Office of Population Control, Family Planning, Women's Empowerment and Child Protection, Batu Bara Regency, Health Office, Kelurahan, Sub-district and cross-sectoral collaboration with other supporting agencies. Accelerating the decline in maternal mortality at the same time also plays a role in increasing maternal health status in the Batu Bara Regency area.